PENINGKATAN KREATIVITAS DAN HASIL BELAJAR IPA MELALUI METODE EKSPERIMEN SISWA MTs NEGERI MAGUWOHARJO - Purna Wijayanti; Tias Ernawati (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2014)
The objective of this study was to improve students’ creativity and science learning outcome at VIII C grade students through a learning experiment method in MTs N Maguwoharjo in academic year 2014/2015. This study was Classroom Action Research (CAR). Observation, test, field notes, questionnaire and documentation were used to gather the data in this study. The results of the study showed that after implementing the experiment method at VIII C class in MTs N Maguwoharjo, the students’ creativity and science learning outcome increased. In pra cycles, the average of the creativity indicator was 49,66%. In the first cycles increased 13,03% became 62,66% and increased to 18,71% became 81,40% in the second cycles. The science-learning outcome increased from 56,97, before the treatment to 66,03 in the first cycles, and became 77 in the second cycles. The number of students who passed the passing grade before the treatment were only 10 students or 31,25%. In first cycles, there were 16 students or 50,00% who passed the passing grade, and there were 25 students or 78,13% in the second cycle.